Les meubles médiévaux aux xviiie et xixe siècles : entre dédain et vision romantique - Cécile Lagane (Perspectives Médiévales)
The Middle Ages has, since the Renaissance period, been considered a poor, dark and uninteresting time. Pieces of furniture have thus been judged boorish, without delicacy or interest. 18th c. joiners have especially singled out the lack of aesthetic qualities of medieval furniture, as opposed to more recent elements, thought «beautiful». The 19th c. medievalist fashion has improved that image of the Middle Ages and its furniture. Decorated pieces have been favoured and put forward, deemed « charming » by the architects in charge of the conservation of the monuments in which they are often kept. However, their analysis is limited to a stylistic interest, often extrapolating from a handful of examples and simplifying the technical aspects of furniture conception. These studies then lead to badly informed representations, depicting an anachronistic and imaginary Middle Ages. The treatment of medieval furniture during the Modern and Contemporary periods, especially during the 18th and 19th c., thus oscillates from a condescending disdain to a patronising romantic vision.